The Role of Gamification in Human Resource Development: A Systematic Review - Yeti, Yeti (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This research explores the impact of gamification in human resource (HR) development with a focus on increasing motivation, engagement, and learning effectiveness in the workplace. Gamification, defined as the integration of game design elements into non-game contexts, has been shown to accelerate the learning process by providing immediate feedback and practice opportunities in a stimulating environment. Through a literature review, it was found that gamification elements such as points, badges, leaderboards, and challenges play a crucial role in increasing employees' intrinsic and extrinsic motivation, as well as optimizing the learning experience. However, challenges in the design of effective gamification programs and adaptation to cultural contexts and individual characteristics are a major concern. This research identifies important strategies for increasing gamification adoption, including stakeholder engagement, effective communication, and flexible design. These findings make a significant contribution to the understanding of how gamification can be integrated into HR practices to improve employee engagement and learning outcomes.